Reproductive biology of Holepyris sylvanidis (Hymenoptera: Bethylidae) - Amante, Marco; Schöller, Matthias; Hardy, Ian C.W.; Russo, Agatino (Elsevier, 2017)
Holepyris sylvanidis (Hymenoptera: Bethylidae) is reported as a cosmopolitan parasitoid of coleopteran including a major pest of stored products, the confused flour beetle Tribolium confusum. The reproductive biology, and hence biocontrol potential of H. sylvanidis is relatively little known. Here we describe and evaluate aspects of egg size, immature development, adult mating behaviour, pre-oviposition time, fecundity, host attack and use, and adult longevity. Our key findings are that ≈72% of presented T. confusum immatures presented to females were attacked and ≈39% of these were fed on destructively with the remainder oviposited onto. First instar host larvae and host pupae were only utilized for feeding, second and third instar larvae were commonly used for either feeding or oviposition while fourth, fifth and sixth instar hosts were almost exclusively used for oviposition. Females usually laid single egg clutches and their average lifetime fecundity was ≈16.5 eggs. Females regularly provisioned with hosts often ceased laying eggs up to several weeks before their death but continued to kill and feed on hosts during this period. Adult longevity was greatly enhanced by the provision of hosts (females) or by non-host food sources (males). We conclude that the inoculative biocontrol potential of H. sylvanidis is likely to be limited by a low realized fecundity and the combination with other control methods in an IPM-approach is needed. Its ability to find and kill hosts may make it more suitable for inundative deployment.